Biodiversity and Ecosystem Functioning in Naturally and Experimentally Assembled Communities - Puppe, Daniel; Dimitrakopoulos, Panayiotis; Lu, Baorong (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint presents two reviews and thirteen research articles dealing with a broad range of biodiversity and ecosystem functioning (BEF) relationships. Each article provides in-depth discussion of the various aspects of BEF relationships in naturally and experimentally assembled communities. This reprint will help to substantially deepen our understanding of BEF interactions and elaborate biodiversity conservation in a changing world. Thus, this publication is not only of interest to scientists in the field, but also for students, university teachers, policymakers, and those who are interested in BEF in general.